Science literacy empowerment for elementary school students at Kera Island Kupang Regency-East Nusa Tenggara - Uslan, U.; Muh, Abdul Syahril; Muhsam, Julhidayat; Aiman, Ummu; Meilani, Dian; Letasado, Muhammad R.; Hasyda, Suryadin; Ahmad, Rizqy Amelia Ramadhaniyah (Journal of Community Service and Empowerment, 2020)
In the 21st century, science literacy is the main competence and indicator to achieve better and more sustainable future. However, limited facilities and resources raise as an issue that have implications to the less optimal application of science literacy empowerment in various regions, including in several areas in East Nusa Tenggara. The objective of this community service is to do mentoring program on the empowerment of science literacy for students at emergency schools in NTT. The target is school-age children living in the island who are subjected to illiteracy due to lack of supporting educational facilities. Methods implemented were through these four stages: (1) initial observation of the area, (2) mapping the problem, (3) socializing the programs, and (4) organizing the science literacy movement. The activities carried out were making educational learning media utilizing plastic waste, creating a reading corner equipped with some interesting books as additional references for children and parents to know about the outside world, creating educational games and actions for the natural surroundings. The results of the observation confirm that the community service program run effectively. It is indicated that the community service project is able to foster students’ interest in reading, writing, and arithmetic. This community service activity is expected to take part in the eradicating illiteracy rate and reducing number of productive age dropouts in East Nusa Tenggara Province.